The Effect of Flipped Learning Based on Mathematical Software on the Behavioral and Cognitive Competencies of Pre-Service Teachers - Khazaie , Milad; Ebadi, Moosa; Azhini , Mehdi; Shahorani Semnani, Ahmad (Management Strategies and Engineering Sciences, 2025)
The present study aimed to examine the effect of flipped learning based on mathematical software on the behavioral and cognitive competencies of pre-service teachers. This research employed a quasi-experimental design with a pretest-posttest-follow-up format, including a control group. The study sought to answer the question: Does flipped learning based on mathematical software influence the professional competencies of mathematics education pre-service teachers at Farhangian University in Tehran Province? The statistical population consisted of all male mathematics education pre-service teachers at Farhangian University in Tehran Province during the 2023–2024 academic year. A total of 40 participants were selected through multistage cluster sampling and randomly assigned to experimental and control groups. The research instrument was Karimi’s (2009) Professional Competency Questionnaire for Teachers. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc test via SPSS version 26. The results indicated that flipped learning based on mathematical software had a positive effect on the behavioral and cognitive competencies of pre-service teachers. Analytical results revealed that the use of mathematical software in flipped learning led to a 20% improvement in social interactions and a 15% increase in students’ conceptual understanding. This learning approach helps students enhance their problem-solving abilities and engage more actively in the learning process.